PENERAPAN SRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 9 PEKANBARU - Miftahnur Hasanah; Maria Erna; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: It has been applied the Power of Two active learning strategy to know the improvement student learning achievement on the subject of Colloid in class XI IPA of Senior High School Number 9 Pekanbaru. The research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of class XI IPA 5 as the experimental class and students of class XI IPA 3 as the control class. Experimental class is a class which was given a treatment by applying active learning strategy type The Power of Two in learning process. The data were analyzed by using t-test. Based on the result of data analysis, it obtained tcount>ttable which is 1.96>1.67. It means that the application of active learning strategy type The Power of Two can improve student learning achievement on the subject of colloid in class XI IPA of Senior High School Number 9 Pekanbaru. The improvement category of student achievement at experiment class was high category with N-gain is 0.78. Meanwhile, the improvement category of student achievement in control class was medium category with N-gain is 0.69.Keywords: Active learning strategy, The Power of Two, Achievement, Colloid